Correlation between MMI performance and OSCE performance - a pilot study - Adetokunbo Oluwasanjo; Thomas Wasser; Richard Alweis (Greater Baltimore Medical Center, 2015)
Objective: The multiple mini-interview (MMI) has been shown to have a positive correlation with early medical school performance, clerkship evaluations, and national licensing examinations. There is limited data on its predictive validity at the postgraduate level. Methods: Six hundred and nineteen internship candidates were interviewed using the MMI format by the internal medicine residency program of The Reading Health System, between September 2011 and February 2014. Fifty-two interns were recruited. Each intern participated in an objective structured clinical examination (OSCE) 3-4 months after the start of the program. The OSCE score of each intern was used as the independent variable to test the relationship with both the MMI interpersonal score and the MMI overall score. Results: There was a moderate positive correlation between the average MMI interpersonal score and the communication score on the OSCE, r=0.384, n=52, p=0.005, and a negligible relationship between the average MMI overall score and the communication score on the OSCE, r=0.175, n=52, p=0.214. Conclusion: The MMI is a useful tool for residency programs to assess interpersonal and communication skills prior to matriculation into residency training. This study provides evidence for its validity in assessing these competencies.